STATE RESPONSIBILITY IN FULFILLING TOURIST HEALTH RIGHTS IN DIVING TOURISM AT BUNAKEN NATIONAL PARK POST-COVID-19 - Х. Рияд; Р. Сьяфаат; И. Коесвахионо; Д. Пуспитавати (Хабаршы. Заң сериясы)
To date, none of the scuba diving operators in Bunaken National Park have obtained the CHSE Protocol certification, despite the government's policy encouraging businesses to adhere to minimum health standards to prevent the resurgence of COVID-19. This study aims to enhance the state's responsibility in upholding tourists' health rights in Bunaken National Park, particularly in the post-COVID-19 scuba diving tourism sector. Employing a socio-legal approach supported by sociology and cultural studies, this research used observation and literature review to collect data. The findings indicate that fulfilling tourists' health rights forms a part of human rights guaranteed by the Indonesian state and governed under both international and national laws. However, the implementation of the CHSE Protocols in the park faces several challenges, including implementation costs, human resources, visitor compliance and discipline, infrastructure, regulatory oversight, economic impacts, and environmental concerns. To better facilitate state responsibility in implementing the CHSE Protocol, this study proposes four government policies to support diving operators in Bunaken National Park: (1) providing subsidies and incentives, (2) offering training and education, (3) enforcing strict oversight and transparency, and (4) fostering multi-party cooperation. These policies aim to enhance compliance with the CHSE Protocol, ensuring the safety and health of tourists and preserving the environment.